Overreaching and overtraining in strength sports and resistance training: A scoping review - Bell, L.; Ruddock, A.; Maden-Wilkinson, T.; Rogerson, D. (Journal of Sports Sciences, 2020)
To date, little is known about overreaching (OR) and the overtraining syndrome (OTS) in strength sports and resistance training (RT) populations. However, the available literature may elucidate the occurrence of both conditions in these populations. A scoping review was conducted. SPORTDiscus, Scopus and Web of Science were searched in a robust and systematic manner, with relevant articles analysed. 1170 records were retrieved during an initial search, with a total of 47 included in the review. Two broad themes were identified during data extraction: 1) overreaching in strength sports; 2) overreaching and overtraining syndrome in RT. Short-term periods of OR achieved with either high-volume or high-intensity RT can elicit functional OR (FOR) but there is also evidence that chronic high-volume and/or intensity RT can lead to non-functional overreaching (NFOR). There is minimal evidence to suggest that true OTS has occurred in strength sports or RT based on the studies entered during this review. More research is needed to develop robust guiding principles for practitioners. Additionally, due to the heterogeneous nature of the existing literature, future research would benefit from the development of practical tools to identify and diagnose the transition from FOR to NFOR, and subsequently OTS in strength athletes and RT populations.